The Barreirinhas Eddies: Stable Energetic Anticyclones in the Near-Equatorial South Atlantic - Simoes-Sousa, Iury T.; Silveira, Ilson Carlos A.; Tandon, Amit; Flierl, Glenn R.; Ribeiro, Cesar H. A.; Martins, Renato P. (Frontiers in Marine Science, 2021)
We explore the Barreirinhas Eddies, submesoscale vortices generated by the North Brazil Current (NBC) off the Barreirinhas Bight (Brazil, centered at 1.75 • S), using vessel-mounted and moored ADCP data, and a Global HYCOM reanalysis. These double-stacked anticyclones with incredibly high Rossby Number (O(10)) occur independently at different depths (high Burger number). Anticyclones with Rossby number greater than unity are unstable according to inviscid linear theory, and hence these submesoscale features are not easily observable at mid latitudes. At these low latitudes, they last about a week, allowing characterization by oceanographic surveys. Our analyses suggest this increased stability is due to the joint effect of strong winds, stratification, proximity to the equator, and topography. Heretofore hypothesized via analytical studies and seen in numerical models, our study confirms this stabilization process in observations, and is also a starting point for the description of the submesoscale dynamics in the NBC domain.